Pengaruh Promosi Terhadap Keputusan Pembelian Produk Sepatu Skechers Pada Toko Skechers Mall Ciputra Seraya Pekanbaru - Dehotman, Khornelis (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
This research was conducted at the Skechers Mall Ciputra Seraya Pekanbaru Store which is located at Jl. Riau No.58, Kampung Baru, Senapelan District, Pekanbaru City. The research aims to determine the effect of promotions on purchasing decisions for Skechers shoe products at the Skechers Mall Ciputra Seraya Pekanbaru Store. the results of simple regression analysis are as follows Y= 10,850 + 0.422X, meaning that when there is an increase in the value of the promotion variable (variable X) by 1 (one) unit, the purchasing decision (variable Y) will increase by 0.422 units. the results of t count > t table are 6,644 > 1,984. The test results show that promotions have a significant effect on purchasing decisions for Skechers shoe products at the Skechers Mall Ciputra Seraya Pekanbaru Store. The coefficient of determination (R Square) is 0.771 or 77%. So it can be concluded that the promotion variable contributes to changes in purchasing decision variables by 77%. while the remaining 23% was influenced by other factors not examined in this study.